PELATIHAN UJI KOMPETENSI MEMPROSES DOKUMEN DANA KAS KECIL PADA SISWA SMK AL-IRSYAD KOTA TEGAL - Hetika, Hetika; Amaliyah, Fitri; Maulidah, Hikmatul; Farida, Ida (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Competence is the ability to behave, think and act consistently as a manifestation of the value of knowledge and skills possessed by someone in carrying out work. The need for competent human resources, according to the needs of the world of work and the industrial world, is currently increasing due to high competition in various aspects of life, including competition to become competent and professional accounting technicians. Competent accounting technicians must meet the minimum standards that can be achieved through a certification test held by the Accounting Technician Professional Certification Institute (LSP-TA). There are several certification schemes for the accounting technician competency test, one of which is the cash fund document management cluster. The method of implementing this community service activity is the lecture, tutorial and discussion method. The results of the activity showed an increase in participants' understanding and skills in processing petty cash fund documents.